2015
DOI: 10.1248/cpb.c14-00638
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile-Containing Phenolic Glucosides from the Leaves of Glochidion acuminatum

Abstract: From the EtOAc-soluble fraction of a MeOH extract of the leaves of Glochidion acuminatum, six new compounds along with five known ones were isolated. The structures of the new compounds were elucidated to be two gallates, a p-hydroxybenzoate and an (S)-2-(4-hydroxycyclohex-1-en-1-yl)acetate of a nitrile-containing phenolic glucoside, methyl 2-(2-hydroxyphenyl)acetate β-D-glucopyranoside, and (S)-methyl 2-[4-sulfooxycyclohex-1-en-1-yl]acetate on the basis of spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Similarly, an HMBC cross‐peak from H‐1′ ( δ H 5.66) to the carbonyl carbon ( δ C 166.6) indicated that the glucose is connected to C‐7 of the p ‐hydroxybenzoyl aglycone. From the above observation, the 1 H‐ and 13 C NMR data of 1 were found to be similar as those of grevilloside J, [ 5 ] except for the replacement of the p ‐hydroxybenzyl group in grevilloside J by the p ‐hydroxybenzoyl group in 1 . The relative configuration of 1 was suggested as shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Similarly, an HMBC cross‐peak from H‐1′ ( δ H 5.66) to the carbonyl carbon ( δ C 166.6) indicated that the glucose is connected to C‐7 of the p ‐hydroxybenzoyl aglycone. From the above observation, the 1 H‐ and 13 C NMR data of 1 were found to be similar as those of grevilloside J, [ 5 ] except for the replacement of the p ‐hydroxybenzyl group in grevilloside J by the p ‐hydroxybenzoyl group in 1 . The relative configuration of 1 was suggested as shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Taken together, the biosynthetic connections within the classes of unusual arbutin ester moieties that we have identified from relictual Proteaceae and more successful taxa from this family are consistent with the chemotaxonomic significance of these unusual molecules (Figure 5). [9,20h,21b,22,24,28–30,31] Specifically, we note that arbutin derivatives containing phenylalanine‐derived esters (blue fragments) have only been identified in Bellendena , Persoonia , Cenarrhenes , Protea , Agastachys , Helicia , Orites , Helicopsis , Grevillea , and Hakea genera to date (Figure 5). All genera are found in the family Proteaceae and these members span the phylogeny, including relictual and more successful members.…”
Section: Resultsmentioning
confidence: 94%
“…Benzoyl acetate or oxidized coumaroyl substituents (e. g., blue fragments within arbutin esters 1 c , 1 d , 1 i – 1 k , and 4 a – 4 d ) likely derive from the biosynthesis of phenylalanine [26] . Robustaside E ( 4 a ) was isolated from Grevillea ‘ Poorinda Queen’, [22] grevillosides L and M ( 4 b and 4 c ) were obtained from Grevillea robusta , [21b] and compound 4 d was found in Protea neriifolia [20h] . All of these are plant species are from the family Proteaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Arg. (Euphorbiaceae) 49 (Figure 9). The degalloylated analogue of 90 had been previously isolated from Ehretia philippinensis A. DC.…”
Section: Resultsmentioning
confidence: 99%